Exploring employability skills initiatives practice in Nigerian technical higher education - Rufai, Ahmed Umar (2015)
The significance of education to national development is widely recognized. it is acknowledged that it influences positively economic growth and development. Further it is argued, the growth and development of this nature hinges predominantly on the quality and quantity of Education (World Bank, 2000). Of recent employers in Nigeria complained that some of the professional graduates from the tertiary institutions have the certificates but lack the practical occupational skills, or job experience. and therefore they are considered incompetent for not being able to relate the theoretical part of their education to the practical working environment in industry. As a result of this, there was 'skill gap' occurring between the demand of employment and the level of educational preparation of graduates. indeed calls for research for a common and effective model or framework of employability that can withstand the test of present day labour market requirement. It was the awareness of this gap in our educational system and the need to bring closer institutions and employer to a more beneficial working relationship that motivated the need for this study. The broad objective of the study is to explore employability skills initiative in Nigerian Technical higher education. Specifically. the aim was to have an in depth investigation on how the tertiary institutions in particular, Universities and Polytechnics in Nigeria seek to enhance graduate employability skills using various approaches. The study was guided by the following five research questions; what is the perception of employability by the academic staff and employers? What skill competence do the employers look for in a contemporary graduate of higher education? What are ways in which the academic department engaged in developing employability skills? How are the employers involved in the planning and implementation of higher education curricula'? And what are the skill competences required to evolve a new framework. The Research method was essentially qualitative, Grounded theory design was selected. The researcher collected documents, conducted semi-structured interviews and recorded observations in cross-section of subject discipline within the academic departments of universities and polytechnics in Nigeria and some selected companies. The study through extensive review of literature, and interviews, captured the collective voices of experts. and professionals from the academics and companies on the development of employability skills, consequently, series of findings emerged. through which a new model of 'ES' evolved. The study findings include among others; that the concept of employability skills underpin two broad areas, subject or discipline based skills and generic skills and it has to do with individual characteristics behavior in terms of occupational skills that makes him work ready; that employers describe an employable graduate as person with flexible attitudes towards work and career, someone with self-theories that create in himself confidence and optimism. Apart from subject skills, the study found that, personal attributes are mostly preferred by employers. These include, interpersonal skills. creativity. teamwork, adaptability, critical thinking/problem solving ability. emotional intelligence. awareness of work environment and attitudes; embedding learning skills into the curricula was found to be more result oriented than other initiatives; other findings includes provision of effective teaching methods and institution employer partnership, improved learning environment and facilities. Finally the study developed a new framework based on USEM account of employability. The new model has four main components. Subject. employment development opportunities, reflection, and employability. In addition to the new proposed framework, the study recommend that both the institutions employers partnership to reconsider a new way of thinking to form considerable flexible commitment from both stakeholders to share the needs, problem, strength, and weakness of educational programmes. The study further recommend the need to overhaul the curricula to systematically address learning of employability, by and large, academic staff, in addition to the subject knowledge, should possess a wide range of teaching methods or strategies.